A compendium of energy costs of physical activities for individuals who use manual wheelchairs - Conger, S. A.; Bassett, D. R. (Adapted Physical Activity Quarterly, 2011)
The purpose of this study was to develop a compendium of wheelchair-related physical activities. To accomplish this, we conducted a systematic review of the published energy costs of activities performed by individuals who use wheelchairs. A total of 266 studies were identified by a literature search using relevant keywords. Inclusion criteria were studies utilizing individuals who routinely use a manual wheelchair, indirect calorimetry as the criterion measurement, energy expenditure expressed as METs or VO2, and physical activities typical of wheelchair users. Eleven studies met the inclusion criteria. A total of 63 different wheelchair activities were identified with energy expenditure values ranging from 0.8 to 12.5 kcal/kg·h. The energy requirements for some activities differed between individuals who use wheelchairs and those who do not. The compendium of wheelchair-related activities can be used to enhance scoring of physical activity surveys and to promote the benefits of activity in this population.